The interrelationship of global market indices and commodities towards the Bursa Malaysia KLCI index / Mohamad Irfan Danish Mohd Roosdi - Mohd Roosdi, Mohamad Irfan Danish (2022)
This research is an attempt to initiate a theoretical interrelationship global market indices and commodities towards KLCI index over the period 2016-2020 in monthly. This research is based on KLCI index while for the independent variables is Dow Jones Industrial Average Index, SSE Composite Index, Hang Seng Index, crude oil price and gold price. This research information is from the database which is investing.com and trading economics website. The research methodology for this analysis is focused on descriptive analysis, correlation analysis, regression analysis and multicollinearity test, autocorrelation analysis and normality analysis. The findings of this study shows that all independent variables are significant to the dependent variable which Bursa Malaysia KLCI Index (KLCI) except Gold Price (GOLD). SSE Composite Index (SSE), Hang Seng Index (HSI), Crude Oil Price (OIL) have a positive relationship with KLCI Index. Dow Jones Industrial Average Index (DJIA) and Gold Price (GOLD) have a negative relationship with KLCI Index.